Plotnostʹ naučnogo teksta i podhody k ee izučeniû - Kotûrova, Mariâ P. (Stylistyka, 2021)
The article deals w ith one of the major properties of scientific discourse - density of content which is regarded as a text category. To study this category different approaches can be used: interdisciplinary,diachronic and synchronie (intertextual and intratextual). Intertextual approach is revealed by mean of the matrix of adjacent meaning of the lexical units displaing the consept of activity.